Economics of pesticides, sustainable food production, and organic food markets - Hall, Darwin C.; Moffitt, L. Joe (Advances in the economics of environmental resources ;, 2002)
Economic assessment of sustainable agricultural practices has continued to mature and to add to our understanding of how we might design policies to ensure an adequate and diverse food supply. This volume presents some of the recent developments and applications in this field and is much more nearly self-contained than typical edited volumes. It provides a comprehensive treatment of topics, including a historical perspective leading to current developments in methods and policy. The introductory chapter presents an early history of research by entomologists and economists, tracing the concept of integrated pest management, the nascent organic food industry, and reviewing pesticide policy options debated over the last several decades. The remainder of the volume is divided into four sections focusing on the economic aspects of production, and related policy issues. These four sections encompass the range of advances in theoretical and applied economic analyses concerned with pesticides and sustainable food markets. Chapters present different methodological, ideological, and geographical perspectives from some of the environmental and agricultural economics concerned with pesticides and sustainable production. This volume includes unique contributions that incorporate international experiences and viewpoints concerning both methods and policy. This volume includes material valuable for students in agricultural economics and environmental science, and is essential reading for economists who conduct research in sustainable agriculture. It is also excellent reference for policy analysts.